Analysis of the different growth years accumulation of flavonoids in Dendrobium moniliforme (L.) Sw. by the integration of metabolomic and transcriptomic approaches - Yuan, Yingdan; Zuo, Jiajia; Zhang, Hanyue; Zu, Mengting; Liu, Sian (Frontiers in Nutrition, 2022)
Dendrobium moniliforme (L.) Sw. is a valuable herbal crop, and flavonoids are primarily distributed as active ingredients in the stem, but the composition and synthesis mechanisms of flavonoids in different growth years are not clear. The accumulation of flavonoids in D. moniliforme from four different years was investigated, using a combined metabolomics and transcriptomics approach in this study. The phenylpropanoid and flavonoid biosynthetic pathways were significantly enriched in the Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analysis of differentially expressed genes (DEGs) and differentially accumulated metabolites (DAMs). The widely targeted metabolomics technique revealed a total of 173 kinds of flavonoid metabolites. The metabolomics data confirmed the trend of total flavonoids (TF) content in stems of D. moniliforme, with chalcone, naringenin, eriodictyol, dihydroquercetin, and other flavonoids considerably up-accumulating in the third year. Twenty DEGs were detected that regulate flavonoid synthesis and the expression of these genes in different growth years was verified using real-time quantitative PCR (qRT-PCR). Furthermore, a comprehensive regulatory network was built for flavonoid biosynthesis and it was discovered that there is one FLS gene, one CCR gene and two MYB transcription factors (TFs) with a high connection with flavonoid biosynthesis by weighted gene co-expression network analysis (WGCNA). In this study, the correlation between genes involved in flavonoid biosynthesis and metabolites was revealed, and a new regulatory mechanism related to flavonoid biosynthesis in D. moniliforme was proposed. These results provide an important reference for the farmers involved in the cultivation of D. moniliforme.